Evolution of research trends and emerging hotspots in bioelectrical impedance analysis over the last two decades: a bibliometric analysis - Chaofeng Niu; Peiyu Zhang; Chao Zhang; Juwei Dong; Hao Liang; Di Xiao; Birong Liu; Lan Wei; Haixia Lai; Jiaqi Ye; Liyong Ma; Lijing Zhang (Journal of the International Society of Sports Nutrition)
Background and objective Over the last two decades, bioelectrical impedance analysis (BIA) has gained popularity as a method for assessing body compartments in nutrition studies, sports medicine, and evaluating hydration levels, fat mass, and fat-free mass variations in both healthy and diseased individuals. This study aims to offer researchers an overview of the research trends in BIA.Methods The data was obtained from the Web of Science Core Collection database. Bibliometric analysis was conducted using a package of R software (Bibliometrix 4.0).Results A total of 9471 articles have been published over the past 20 years, with an average annual growth rate of 10.1%. The research field primarily focuses on nutrition and dietetics, followed urology and nephrology, endocrinology and metabolism, general and internal medicine, engineering, geriatrics and gerontology, sport sciences, cardiovascular system and cardiology, physiology and science and technology-other topics. The research hotspots of BIA over the past 20 years have transitioned from “water” to “fat,” and subsequently to “sarcopenia.” “Sarcopenia” and “phase angle” (PhA) have emerged as recent research hotspots in the field of BIA.Conclusion A total of 9471 articles have been published over the past 20 years, with an average annual growth rate of 10.1%. Nutrition and dietetics have consistently been the primary research areas in the field of BIA. “Sarcopenia” and “PhA” have emerged as recent research hotspots in the field of BIA. The application of BIA in clinical practice still holds significant untapped potential.